Arrhythmic events pertinent with antidepressants: a Bayesian disproportional analysis mining the FDA Adverse Event Reporting System database - Cao, Shan; Huang, Zhuoshan; Yang, Wenjie; Yang, Saijia; Chen, Xi; Xie, Xujing (Frontiers in Psychiatry, 2025)
ObjectiveThe aim of this study was to investigate pharmacovigilance (PV) and make pairwise comparisons on arrhythmic events among antidepressants from the US Food and Drug Administration Adverse Event Reporting System (FAERS).MethodsRecords regarding antidepressants treating depression and major depression from the first quarter of 2015 to the third quarter of 2023 documented in the FAERS database were harvested. The primary endpoint of this study was PV for arrhythmic events, including QT prolongation/Torsades de Pointes (TdP), atrial fibrillation (AF), heart block, and ventricular arrhythmia. The secondary endpoints comprised the pairwise comparisons on constituent ratio and severity of outcomes of drugs of interest on the above four diseases.ResultUltimately, 746,507 records were eligible for analysis. PV for QT interval prolongation/TdP was identified for citalopram [proportional reporting ratio (PRR) = 2.13, 95% confidence interval (CI): 1.89 to 2.40, reporting odds ratio (ROR) = 2.14, 95% CI: 1.90 to 2.40, IC = 0.98, 95% CI: 0.80 to 1.12], escitalopram (ROR = 1.72, 95% CI: 1.52 to 1.96, IC = 0.71, 95% CI: 0.51 to 0.86), fluoxetine (ROR = 1.39, 95% CI: 1.21 to 1.60, IC = 0.43, 95% CI: 0.21 to 0.60), and quetiapine (ROR = 1.58, 95% CI: 1.30 to 1.91, IC = 0.63, 95% CI: 0.31 to 0.85). In terms of AF, PV was detected in citalopram (ROR = 1.82, 95% CI: 1.44 to 2.30, IC = 0.78, 95% CI: 0.41 to 1.05), escitalopram (ROR = 1.34, 95% CI: 1.03 to 1.74), sertraline (ROR = 1.32, 95% CI: 1.07 to 1.64, IC = 0.35, 95% CI: 0.01 to 0.59), and fluoxetine (ROR = 1.68, 95% CI: 1.32 to 2.13, IC = 0.68, 95% CI: 0.29 to 0.95). With regard to heart block, PV was detected in citalopram (ROR = 1.37, 95% CI: 1.05 to 1.80) and mirtazapine (ROR = 1.40, 95% CI: 1.03 to 1.90). Regarding ventricular arrhythmia, PV was detected in citalopram (ROR = 1.55, 95% CI: 1.19 to 2.02, IC = 0.58, 95% CI: 0.15 to 0.88), escitalopram (ROR = 1.51,95% CI: 1.16 to 1.97, IC = 0.54, 95% CI: 0.12 to 0.85), and quetiapine (PRR = 2.39, 95% CI: 1.75 to 3.25, ROR = 2.39, 95% CI: 1.75 to 3.26, IC = 1.17, 95% CI: 0.67 to 1.54).ConclusionCitalopram and escitalopram [classified as selective serotonin reuptake inhibitors (SSRIs)] exhibited the strongest correlations with arrhythmic occurrences. Quetiapine [classified as a second-generation antipsychotic (SGA)] demonstrated higher risk and worse prognosis on QT prolongation/TdP and ventricular arrhythmic events. Venlafaxine and duloxetine [classified as serotonin-norepinephrine reuptake inhibitors (SNRIs)] did not show any PV of any arrhythmia and had lower risks and a lower degree of adverse events compared with the rest. Certainly, more head-to-head related studies are merited.